Rethinking reverse logistics: role of additive manufacturing technology in metal remanufacturing. Issue 1 (20th January 2020) - Strong, Danielle; Kay, Michael; Wakefield, Thomas; Sirichakwal, Issariya; Conner, Brett; Manogharan, Guha
Abstract : Purpose: Although the adoption of metal additive manufacturing (AM) for production has continuously grown, in-house access to production grade metal AM systems for small and medium enterprises (SMEs) is a major challenge due to costs of acquiring metal AM systems, specifically powder bed fusion AM. On the other hand, AM technology in directed energy deposition (DED) has been evolving in both: processing capabilities and adaptable configuration for integration within existing traditional machines that are available in most SME manufacturing facilities, e.g. computer numerical control (CNC) machining centers. Integrating DED with conventional processes such as machining and grinding into Hybrid AM is well suited for remanufacturing of metal parts. The paper aims to discuss these issues. Design/methodology/approach: Classical facility location models are employed to understand the effects of SMEs adopting DED systems to offer remanufacturing services. This study identifies strategically located counties in the USA to advance hybrid AM for reverse logistics using North American Industry Classification System (NAICS) data on geographical data, demand, fixed and transportation costs. A case study is also implemented to explore its implications on remanufacturing of high-value parts on the reverse logistics supply chain using an aerospace part and NAICS data on aircraft maintenance, repair and overhaul facilities. Findings: The results identify the candidate counties, their allocations, allocated demand and total costs. Offering AM remanufacturing services to traditional manufacturers decreases costs for SMEs in the supply chain by minimizing expensive new part replacement. The hubs also benefit from hybrid AM to repair their own parts and tools. Originality/value: This research provides a unique analysis on reverse logistics through hybrid AM focused on remanufacturing rather than manufacturing. Facility location using real data is used to obtain results and offers insights into integrating AM for often overlooked aspect of remanufacturing. The study shows that SMEs can participate in the evolving AM economy through remanufacturing services using significantly lower investment costs.